Pengaruh Religiusitas, Norma Subjektif, Dan Perceived Behavioral Control Tehadap Minat Beli Skincare Berlabel Halal Di Kota Malang - Hidayah, Riska Anne Dwi Nur; Basalamah, Muhammad Ridwan; Rahmawati, Rahmawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to examine the effect of religiosity, subjective norms and perceived behavioral control on buying interest in halal-labeled skincare in Malang City. This research uses a quantitative approach. The population in this study were people in Malang City. The sampling method in this study used accidental sampling, in this study the sample amounted to 70 respondents. While the data analysis used is Multiple Linear Regression with the help of SPSS 25.0. The conclusions drawn are that religiosity and subjective norms have a positive and significant effect on buying interest, and perceived behavioral control has a negative and significant effect on buying interest in halal-labeled skincare in Malang City. Keywords: Religiosity, Subjective Norms and Perceived Behavioral Control, Purchase Intention